STATISTICAL OPTIMIZATION OF MEDIUM COMPOSITION FOR MELANIN PRODUCTION BY LOCAL ISOLATE OF STREPTOMYCES ATROVIRENS TA4 - A-Rubaye, T. S.; Luti, K. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
Melanin pigment has broad applications in medicine, cosmetics, and agriculture. In this study, Streptomyces atrovirens TA4, a soil isolate was used for the first time to produce bioactive melanin pigment. This work mainly focuses on media optimization and using statistics to obtain optimum concentrations of the medium composition for maximum pigment production. Starch casein broth was the best melanin pigment-producing medium (127.6 mg/L ) among 8 tested media. Central composite design analysis using (Design-Expert-13), a statistics-based method, revealed casein as the most significant factor affecting melanin production with an F-value of 1878.8 and the model exhibited good fitting, with a correlation coefficient of 0.88. An experimental model was generated according to the values of response resolved in the designed experiment and the R2 value was 0.8174. The suggested optimal concentrations of (starch, casein, KNO3 and Nacl) were (20 gŁ, 3 gŁ, 0.5 gŁ and 1 gŁ), respectively. The model's accuracy was determined and results showed that the melanin pigment yield was 123 mgŁ which was Approximately matches the predicted value (109 mgŁ).